Magyarország mezőgazdaságának jövedelmezősége az agrártámogatások tükrében 2006 és 2015 közötti időszakban = The profitability of hungarian agriculture in the light of subsidies in period 2006–2015 - Sipiczki, Zoltán; Rajczi, Alexandra (Közép-Európai Közlemények, 2018)
Examining profitability is a key issue for the agricultural sector. The basic idea behind this article is that, in addition to examining the profitability of the examined agricultural sector in Hungary, it is worth examining the traditional profitability indicators as well as the specific factors determining the profitability of the agricultural sector. We are looking for an answer as to which part of the domestic agricultural business is what is competitive and, even without subsidies, a profitable category. We will examine how far the size of farms and the production direction are to change the profitability of individual farmers and agricultural subsidies. However, an investigated group, especially small agricultural businesses, considered this size range as a highly heterogeneous group. The study analyzes domestic agricultural enterprises in the database of the Farming Information System operated by the Agricultural Research Institute. The analysis was performed with statistically closed time series data.